PENGARUH PEMBELAJARAN KOMPETENSI DASAR KETERAMPILAN, PRAKTIK KERJA LAPANGAN, DAN SELF EFFICACY TERHADAP KESIAPAN KERJA SISWA DI SMK NEGERI TAKALAR TAHUN 2023 - Ariyanto; Amiruddin; Faizal Amir (Program Studi S2 Pendidikan Teknologi dan Kejuruan, 2023)
This study aims to find out: (1) an overview of students' basic competency learning skills at Takalar State Vocational School, (2) an overview of Student Field Work Practices (PKL) at Takalar State Vocational School, (3) an overview of Student Self-Efficacy at Takalar State Vocational School, (4) an overview of student work readiness at Takalar State Vocational School, (5) the effect of basic skills competency learning on student work readiness at Takalar State Vocational School, (6) the effect of Field Work Practices (PKL) on student work readiness at Takalar State Vocational School, (7) the effectof Self-Efficacy On the work readiness of students at Takalar State Vocational School, (8) the joint effect of learning basic competency skills, field work practices, and self-efficacy on student work readiness at Takalar State Vocational School. This type of research is quantitative research with the Expost Facto method. The samplein the study was 123 students of class XII. Research data obtained by documentation and questionnaire techniques. The data analysis technique used was descriptivestatistical analysis, inferential statistics and hypothesis testing using the SPSS program. The research results show that; (1) students' basic competency learning skills are in the